Identification of powdery mildew on Prunus rufoides in China, caused by Podosphaera prunigena - WANG, Zhilong; LI, Wen; HE, Yueqiu; LIU, Feng; FENG, Kai; LIU, Liang; FU, Tao; YE, Qi; WANG, Guoliang (Phytopathologia Mediterranea, 2024)
Prunus rufoides is a deciduous wild tree, native to China, which is also used as an ornamental. From late March to December in the years 2018 to 2023, P. rufoides plants growing in Siming Mountain (29°71’08”N, 121°15’12”E), Ningbo, Zhejiang Province, were severely affected by powdery mildew. The disease initially emerged in late March each year, and was characterized as white, irregular mycelial patches on the adaxial surfaces of young leaves. Between July and August, the powdery mildew colonies on affected parts of leaves disappeared, leaving only irregular yellow-brown spots. The disease recurred in September and persisted until late December. Chasmothecia containing asci and ascospores were observed on the leaves in December. Morphological analyses of the chasmothecia indicated a Podosphaera sp. as the causative agent. Molecular identification, based on the internal transcribed spacer (ITS) region (primers ITS4/ITS5) confirmed the identity of the pathogen as Podosphaera prunigena. Koch’s postulates were fulfilled by inoculation tests in which the same pathogen was identified from the inoculated leaf tissue. This study represents the first report confirming the powdery mildew disease on P. rufoides in China to be caused by P. prunigena.